MeqSilhouette v2: spectrally resolved polarimetric synthetic data generation for the event horizon telescope. Issue 1 (26th February 2022) - Natarajan, Iniyan; Deane, Roger; Martí-Vidal, Iván; Roelofs, Freek; Janssen, Michael; Wielgus, Maciek; Blackburn, Lindy; Blecher, Tariq; Perkins, Simon; Smirnov, Oleg; Davelaar, Jordy; Moscibrodzka, Monika; et al.
ABSTRACT: We present MeqSilhouette v2.0 (MeqSv2), a fully polarimetric, time-and frequency-resolved synthetic data generation software for simulating millimetre (mm) wavelength very long baseline interferometry (VLBI) observations with heterogeneous arrays. Synthetic data are a critical component in understanding real observations, testing calibration and imaging algorithms, and predicting performance metrics of existing or proposed sites. MeqSv2 applies physics-based instrumental and atmospheric signal corruptions constrained by empirically derived site and station parameters to the data. The new version is capable of applying instrumental polarization effects and various other spectrally resolved effects using the Radio Interferometry Measurement Equation (RIME) formalism and produces synthetic data compatible with calibration pipelines designed to process real data. We demonstrate the various corruption capabilities of MeqSv2 using different arrays, with a focus on the effect of complex bandpass gains on closure quantities for the EHT at 230 GHz. We validate the frequency-dependent polarization leakage implementation by performing polarization self-calibration of synthetic EHT data using PolSolve. We also note the potential applications for cm-wavelength VLBI array analysis and design and future directions.